PERS SEBAGAI MEDIA PERJUANGAN KEMERDEKAAN DALAM FILM BUYA HAMKA VOL 1 - Alpiodita, Yurin; Sukmawati, Lilis (IAKN AMBON, 2024)
Journalists or reporters have a very important role in society. With the press, various kinds of information can be disseminated for the sake of public knowledge about an important event or just information that is obtained. This research is entitled